Anesthesia-Sepsis-Associated Alterations in Liver Gene Expression Profiles and Mitochondrial Oxidative Phosphorylation Complexes - Osuru, Hari Prasad; Paila, Umadevi; Ikeda, Keita; Zuo, Zhiyi; Thiele, Robert H. (Frontiers in Medicine, 2020)
Background: Hepatic dysfunction plays a major role in adverse outcomes in sepsis. Volatile anesthetic agents may protect against organ dysfunction in the setting of critical illness and infection. The goal of this study was to study the impact of Sepsis-inflammation on hepatic subcellular energetics in animals anesthetized with both Propofol (intravenous anesthetic agent and GABA agonist) and Isoflurane (volatile anesthetic i.e., VAA). Methods: Sprague-Dawley rats were anesthetized with Propofol or isoflurane. Rats in each group were randomized to celiotomy and closure (control) or cecal ligation and puncture “CLP” (Sepsis-inflammation) for 8 h. Results: Inflammation led to upregulation in hepatic hypoxia-inducible factor-1 in both groups. Rats anesthetized with isoflurane also exhibited increases in bcl-2, inducible nitric oxide synthase, and heme oxygenase-1(HO-1) during inflammation, whereas rats anesthetized with Propofol did not. In rats anesthetized with isoflurane, decreased mRNA, protein (Complex II, IV, V), and activity levels (Complex II/III,IV,V) were identified for all components of the electron transport chain, leading to a decrease in mitochondrial ATP. In contrast, in rats anesthetized with Propofol, these changes were not identified after exposure to inflammation. RNA-Seq and real-time quantitative PCR (qPCR) expression analysis identified a substantial difference between groups (isoflurane vs. Propofol) in mitogen-activated protein kinase (MAPK) related gene expression following exposure to Sepsis-inflammation. Conclusions: Compared to rats anesthetized with Propofol, those anesthetized with isoflurane exhibit more oxidative stress, decreased oxidative phosphorylation protein expression, and electron transport chain activity and increased expression of organ-protective proteins.